2009
DOI: 10.1002/ccd.22015
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous versus surgical revascularization for multivessel coronary artery disease: A single center 10 year follow‐up of SOS trial patients

Abstract: These findings suggest that patients with multivessel coronary artery disease technically suitable for either stent supported PCI or CABG have very similar 10 year outcomes with respect to mortality, angina class, LVEF, and MACCE other than RR. Excess RR following PCI predominantly occurs in early years and is numerically lower following PCI in years 5-10. This underscores the need for longer-term follow up from randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…10 Mortality has been the same, however, except for patients with diabetes. 11,12 A recently published randomized multicenter SYNTAX trial 10 confirmed previous studies 13,14 by showing that PCI is not inferior to CABG in regard to mortality for patients with left main or 3-vessel coronary artery diseases who are suitable candidates for both interventions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…10 Mortality has been the same, however, except for patients with diabetes. 11,12 A recently published randomized multicenter SYNTAX trial 10 confirmed previous studies 13,14 by showing that PCI is not inferior to CABG in regard to mortality for patients with left main or 3-vessel coronary artery diseases who are suitable candidates for both interventions.…”
Section: Discussionmentioning
confidence: 82%
“…Statistical Package for the Social Sciences (SPSS Inc, Chicago, Ill) and SAS (SAS Institute, Inc, Cary, NC) software packages were used to calculate age-adjusted rate. 13 Quantitative variables were expressed as mean AE SD. Independent samples t test was used for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5 RCTs [ 5 , 14 – 17 ] reporting data from 3013 participants and 4 OSs [ 18 21 ] of 5608 enrolled participants were included for analysis. A flowchart indicating selection strategy was showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, we utilized random-effects model and heterogeneity test to reduce statistics bias. What’s more, there was one included RCTwith9.6 ± 0.85 years follow-up on average [ 14 ], and another included OS with candidates who were all diabetic and MVCA patients [ 21 ]. We performed sensitivity and subgroup analyses showing that all results remained robust when excluding these 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…, &Caicedo , 1984); incluso las técnicas descritas pueden ser complementarias después de una intervención fallida percutánea(Sarno, Garg , Onuma, & Gutierrez, 2010).Los resultados son similares al utilizar cualquier técnica, sin embargo se recomienda evaluar el compromiso de vasos obstruidos lo que denotaría la severidad de la enfermedad, a mayor número de vasos es aconsejable utilizar técnicas quirúrgicas(Buszman, Wiernek, & Szymanski, 2009), todas las instituciones tienen en sus áreas de urgencias y hospitalización sistemas de atención y de referencia-contra referencia para este tipo de patologías, respaldados por guías de manejo y protocolos que se actualizan periódicamente.En Colombia los procedimientos cardiovasculares han sido descritos ampliamente en los últimos 40 años, y las guías de práctica clínica para el manejo del infarto agudo de miocardio han tenido actualizaciones recientes (2017), así como estudios…”
unclassified